Efektivitas Penggunaan Pellet Berbasis Rumput Odot Dan Kombinasinya Terhadap Performans Kelinci Rex Jantan - Jalu Andika Kurniawan; Eudia Christina Wulandari; Purwadi Purwadi (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2022)
Abstract This study aims to determine the effectiveness of using Dwarf Elephant Grass -based pellets and the combination on the performance of male Rex Rabbits. This study used 20 male Rex rabbits with an average body weight of 1222.61 ± 49.39 g/head (cv ±4,04%). The design used was a completely randomized design (CRD) with a unidirectional pattern with 4 treatments and 5 replications. The rations given were “Citra Feed” comercial pellets and Dwarf Elephant Grass -based pellets. The treatments were T0 (100% commercial pellet), T1 (70% commercial pellet + 30% Dwarf Elephant Grass pellet), T2 (30% commercial pellet + 70% Odot pellet), T3 (100% Dwarf Elephant Grass pellet). The results of statistical analysis showed that using Dwarf Elephant Grass -based pellets had a very significant effect on dry matter (P<0.01), and had a significant effect on ADG and feed cost per gain (P<0.05), not sicnificantly different to feed convetion ratio (P>0,05). From the results of the study, it was concluded that using Dwarf Elephant Grass based pellets as much as 30% of the total ration increased the performance of male Rex Rabbits. Keywords: dwarf elephant grass, pellets, performance, Rex Rabbit